E-025 Evaluation of a computer modeling system for flow diverter treatment planning. (22nd July 2019) - Baccin, C; Babiker, H
Abstract : Introduction: Flow diversion is an effective treatment option for cerebral aneurysms (CAs). Appropriately sizing flow diverters (FDs) is critical for treatment success. 1 However, FDs can be difficult to size. They can elongate by more than 50% of their nominal length after deployment and vessel diameters may vary considerably along the trajectory of the vessel. 2 Current convention does not address these challenges well. Here we present our preliminary evaluation of a computer modeling system that uses real-time FD deployment simulations and the three-dimensional (3D) model of the patient's vessel to size FDs. Materials and methods: The computational modeling system was evaluated for a series of 7 CAs that were planned for treatment with the Pipeline Flex (Medtronic, USA) FD. Evaluation was performed retrospectively in 2 CAs and prospectively in 5 CAs. In each case, rotational angiography image data were first uploaded to the SurgicalPreview® (EndoVantage, USA) computational modeling software. The image data were then segmented by the software and used to reconstruct a 3D model of the vessel. Next, FD sizes that were being considered for treatment were virtually deployed into the vessel model in real-time and the appropriate FD size for each vessel was selected. Simulated and clinical FD deployments were then compared using post-treatment angiography images. Results: Good qualitative agreement was observed between simulated and clinical FD deployments based on device length and aneurysmal neck-coverage, as shown in figure 1. In the prospective cases, the simulations helped narrow the list of device sizes being considered and improved confidence in device selection. Conclusion: Our early experience with the computational modeling system suggests that the technology can potentially accurately predict FD behavior and facilitate the selection of the optimal FD size for a vessel. The technology has great potential to reduce technical complications during FD treatment and improve treatment outcomes. References: Aquarius R, et al. 'The Importance of Wall Apposition in Flow Diverters. Neurosurgery April 2018. Narata AP, et al. 'Early Results in Flow Diverter Sizing by Computational Simulation: Quantification of Size Change and Simulation Error Assessment'. Oper Neurosurg 2018: 9. Disclosures: C. Baccin: None. H. Babiker: 4; C; EndoVantage. 5; C; EndoVantage.